Traditional chinese medicine to prevent and treat diabetic erectile dysfunction - Feng, Yanfei; Shi, Tianhao; Fu, Yuli; Lv, Bodong (Frontiers in Pharmacology, 2022)
Diabetic erectile dysfunction (DED) is one of the most common complications of diabetes mellitus. However, current therapeutics have no satisfactory effect on DED. In recent years, traditional Chinese medicine (TCM) has shown good effects against DED. By now, several clinical trials have been conducted to study the effect of TCM in treating DED; yet, the underlying mechanism is not fully investigated. Therefore, in this review, we briefly summarized the pathophysiological mechanism of DED and reviewed the published clinical trials on the treatment of DED by TCM. Then, the therapeutic potential of TCM and the underlying mechanisms whereby TCM exerts protective effects were summarized. We concluded that TCM is more effective than chemical drugs in treating DED by targeting multiple signaling pathways, including those involved in oxidation, apoptosis, atherosclerosis, and endothelial function. However, the major limitation in the application of TCM against DED is the lack of a large-scale, multicenter, randomized, and controlled clinical trial on the therapeutic effect, and the underlying pharmaceutical mechanisms also need further investigation. Despite these limitations, clinical trials and further experimental studies will enhance our understanding of the mechanisms modulated by TCM and promote the widespread application of TCM to treat DED.